SEPEDA SEBAGAI ALAT TRANSPORTASI RAMAH LINGKUNGAN - Sonya Sidjabat (Institut Transportasi dan Logistik Trisakti, 2016)
Bicycling once again has become a trend in big cities, including Jakarta. As a form of common transportation in the world, bicycling starts to gain its fame by government’s efforts in some cities in emphasizing the bicycling activity through special programs. The amount of bicycles, almost twice the public transportations, but as mentioned, to emphasize the bicycling activites, countries such as Netherlands, Denmark, Belgia and German have been developing special roads for bicycle riders, each with equal rights to use the roads separately from the motors/cars riders. With separated parking lot, bicycle rents with bail are given back, even special bicycle guarantees, everything is cultivated for the sake of increasing yet enhancing bicycling activity. In big cities like Jakarta, the bikers’ community has convinced workers to ride their bikes when going to work. This program is called bike to work (B2W). One of the concrete action we can perform to prevent global warming is to lure others to apply the “safe transportations” in their everyday lives. Bicycle, is one of them.